Lithospheric Delamination Beneath the Southern Puna Plateau Resolved by Local Earthquake Tomography. Issue 10 (28th September 2020) - Chen, Jing; Kufner, Sofia‐Katerina; Yuan, Xiaohui; Heit, Benjamin; Wu, Hao; Yang, Dinghui; Schurr, Bernd; Kay, Suzanne
Abstract: We present a local earthquake tomography to illuminate the crustal and uppermost mantle structure beneath the southern Puna plateau and to test the delamination hypothesis. Vp and Vp/Vs ratios were obtained using travel time variations recorded by 75 temporary seismic stations between 2007 and 2009. In the upper crust, prominent low Vp anomalies are found beneath the main volcanic centers, indicating the presence of magma and melt beneath the southern Puna plateau. Beneath the Moho at around 90‐km depth, a strong high Vp anomaly is detected just west of the giant backarc Cerro Galan ignimbrite caldera. This high Vp anomaly is only resolved if earthquakes with an azimuthal gap up to 300° are included in the inversion. However, we show through data subset and synthetic tests that the anomaly is robust due to our specific station‐event geometry and interpret it as a delaminated block of lower crust and uppermost mantle lithosphere under the southern Puna plateau. The low velocities in the crust are interpreted as a product of the delamination event that triggered the rise of fluids and melts into the crust and induced the high topography in this part of the plateau. The tomography also reveals the existence of low‐velocity anomalies that link arc magmatism at the Ojos del Salado volcanic center with slab seismicity clusters at depths of about 100 and 150 km and support fluid transport in the mantle wedge due to dehydration reaction within the subducted slab. Key Points: A local earthquake tomography is performed for the southern Puna plateau and adjacent region A high mantle Vp anomaly beneath Cerro Galan provides evidence for lithospheric delamination A low Vp zone is observed beneath Ojos del Salado, reflecting fluid transport supplied by slab dehydration at two depths